The shape and flexibility of tropomyosin coiled coils: implications for actin filament assembly and regulation - Li, Xiaochuan (Edward); Holmes, Kenneth C.; Lehman, William; Jung, HyunSuk; Fischer, Stefan (Journal of molecular biology, 2010)
Wrapped superhelically around actin filaments, the coiled-coil α-helices of tropomyosin regulate muscle contraction by cooperatively blocking or exposing myosin-binding sites on actin. In non-muscle cells, tropomyosin additionally controls access of actin-binding proteins involved in cytoskeletal actin filament maintenance and remodeling. Tropomyosin's global shape and flexibility play a key role in the assembly, maintenance, and regulatory switching of thin filaments yet remain insufficiently characterized. Here, electron microscopy and molecular dynamics simulations yielded conformations of tropomyosin closely resembling each other. The electron microscopy and simulations show that isolated tropomyosin has an average curved conformation with a design well matched to its superhelical shape on F-actin. In addition, they show that tropomyosin bends smoothly yet anisotropically about its distinctive helically curved conformation, without any signs of unfolding, chain separation, localized kinks, or joints. Previous measurements, assuming tropomyosin to be straight on average, mistakenly suggested considerable flexibility (with persistence lengths only ∼3 times the protein's length). However, taking the curved average structure determined here as reference for the flexibility measurements yields a persistence length of ∼12 lengths, revealing that tropomyosin actually is semirigid. Corresponding simulation of a triple mutant (A74L-A78V-A81L) with weak actin affinity shows that it lacks shape complementarity to F-actin. Thus, tropomyosin's pre-shaped semirigid architecture is essential for the assembly of actin filaments. Further, we propose that once bound to thin filaments, tropomyosin will be stiff enough to act as a cooperative unit and move on actin in a concerted way between known regulatory states.